Methods of resource room management for teachers of learning disabilities in English language in light of some variables - Mohamad Ahmad Saleem Khasawneh (Universitas Islam Sultan Agung, 2021)
This study aimed at identifying the methods of managing the resource room for teachers of English language learning disabilities in the light of some variables. The study population consisted of all (60) teachers of English language learning disabilities in the upper basic stage in Irbid Governorate. The sample of the study consisted of (30) female and male teachers. The study used the descriptive methodology, for which a questionnaire was developed to collect and test data. The results of the study showed that the democratic method ranked first with a mean score of (4.13) and a standard deviation of (0.59), and the autocratic method came in the second rank with a mean score of (2.30) and a standard deviation of (0.57). The laissez-faire method came in the last rank with a mean score of (1.96), and a standard deviation of (1.96).